Obesity and Breast Cancer: Role of Leptin - Sánchez-Jiménez, Flora; Pérez-Pérez, Antonio; de la Cruz-Merino, Luis; Sánchez-Margalet, Víctor (Frontiers in Oncology, 2019)
Obesity-related breast cancer is an important threat that affects especially post-menopausal women. The link between obesity and breast cancer seems to be relying on the microenvironment generated at adipose tissue level, which includes inflammatory cytokines. In addition, its association with systemic endocrine changes, including hyperinsulinemia, increased estrogens levels, and hyperleptinemia may be key factors for tumor development. These factors may promote tumor initiation, tumor primary growth, tissue invasion, and metastatic progression. Although the relationship between obesity and breast cancer is already established, the different pathophysiological mechanisms involved are not clear. Obesity-related insulin resistance is a well-known risk factor for breast cancer development in post-menopausal women. However, the role of inflammation and other adipokines, especially leptin, is less studied. Leptin, like insulin, appears to be a growth factor for breast cancer cells. There exists a link between leptin and metabolism of estrogens and between leptin and other factors in a more complex network. As a result, obesity-associated hyperleptinemia has been suggested as an important mediator in the pathophysiology of breast cancer. On the other hand, recent data on the paradoxical effect of obesity on cancer immunotherapy efficacy has brought some controversy, since the proinflammatory effect of leptin may help the effect of immune checkpoint inhibitors. Therefore, a better knowledge of the molecular mechanisms that mediate leptin action may be helpful to understand the underlying processes which link obesity to breast cancer in post-menopausal women, as well as the possible role of leptin in the response to immunotherapy in obese patients.